Lessons Learned from Long-Term Cycling Experiments with Pouch Cells with Li-Rich and Mn-Rich Positive Electrode Materials. Issue 6 (1st June 2022) - Väli, Ronald; Aftanas, Stuart; Eldesoky, A.; Liu, Aaron; Taskovic, Tina; Harlow, Jessie E.; deGooyer, Jack; Phattharasupakun, Nutthaphon; Ouyang, Dongxu; Rathore, Divya; Cormier, Marc M. E.; Johnson, Michel B.; et al.
Abstract : In this work, the performance of commercial (250–300 mAh) Li1.11 Ni0.34 Mn0.53 Al0.02 O2 /graphite (LNMA) and Li1.167 Ni0.183 Mn0.558 Co0.092 O2 /graphite (LNMC) pouch cells was evaluated using different cycling drive profiles, temperatures, formation voltages, cycling upper and lower cut-off voltages. A variety of electrolyte additives and additive combinations were tested in the LNMA cells. The best performing electrolyte in high voltage LNMA cells (4.6 V upper cut-off) was Control + 2% fluoroethylene carbonate (FEC) + 1% lithium difluorophosphate (LFO) + 1% lithium difluoro(oxalato)borate (LiDFOB) with 87% capacity retention after 720 cycles. LNMA cells cycled to 4.25 V and LNMC cells cycled to 4.44 V at 40 °C were able to cycle for 1000 cycles before reaching 80% capacity. These materials can have surprisingly good high-voltage performance, but we stress that a fundamental breakthrough that can eliminate the voltage fade that is ubiquitous in Li-rich and Mn-rich materials is necessary to make Li-rich materials competitive with existing cell chemistries. We demonstrate that the high specific capacity of Li-rich materials can be deceptive when making conclusions about the energy density of Li-rich/graphite full cells. Hopefully, these results can set a baseline for other researchers in the Li-rich space.